Teacher's Role Program in Inclusive Education to Achieve Sustainable Development Goals (SDGs) - Khayati, Nurul Ani; Muna, Faizatul; Oktaviani, Eling Diar; Hidayatullah, Ahmad Fauzan (Universitas Negeri Padang, 2020)
The phenomenon of problems relating to students with special needs or students who need teaching in their studies more deeply. The student will later follow the regular learning system, especially in elementary schools, which demand to hold inclusive learning that unites the teaching and learning process between regular students (normal students) and students with special needs. Therefore the competence of teachers in schools will be demanded to be more profound in teaching students with special needs. The methodology used in this study uses the method of library (library research), while collecting data by examining and exploring a number of journals, books, and several articles where data sources or other information are relevant (related) to the appropriate study. The purpose of this study is to analyze the role of teachers in inclusive education to students with special needs. The results showed that the teacher had done adaptive learning for children who had difficulty learning by adjusting the conditions of the students themselves, the adjustment was related to the method of strategy, material, learning tools/media, and learning environment.Keywords: Education, Inclusive, Teacher, Role